Investigation of Peroxide, Acidity, and Thermal Stability of Oils Used to Make Falafel in Arak, Iran in 2018 - Mostafa Delavar; Atefeh Navabi; Ahmad Abdollahi; Hasan Mahmodi; Ali Jamshidi (Mazandaran University of Medical Sciences, 2020)
Introduction and purpose: Due to the increasing consumption of fried foods, it is important to check the quality of the oil used for frying to maintain the health of consumers. Therefore, this study aimed to determine the amount of peroxide, acidity, and thermal stability of the oils used in Falafel stores in Arak, Iran. Methods: This cross-sectional study was performed on 25 traditional units and 2 industrial units producing Falafel in Arak, Iran, during 2018. In total, 50 and 3 samples were obtained from traditional (two samples from each unit) and industrial units, respectively, to determine the peroxide and acidity based on the standardized methods No. 4178 and 4179. Moreover, thermal stability was measured using the Rancimat device. The data were analyzed using SPSS  software (version 22) through with Wilcoxon tests and correlated t-test. Results: The results showed that the peroxide and acidity of the used oils were higher than the allowable limit, and the thermal stability was lower than the allowable limit. According to the obtained data, the samples were rejected in terms of peroxide content of 72%, acidity of 68%, and thermal stability of 98%. Conclusion: These findings show the inefficiency of the oils used in Falafel stores in Arak, Iran. In addition, the shelf-life of half-cooked Falafel should be reduced.